Developing the learning to learn competence through the integration of learning styles: theoretical and applied approaches - SEREMET, Ileana Simona (Acta et Commentationes, Sciences of Education, 2025)
Aligned with contemporary trends in education, there is a growing emphasis on the development of transversal competencies to support long-term learning. Starting from certain theoretical premises regarding learning, the paper proposes conceptual integration models between learning styles, the self-regulated learning model, and the development of learning-to-learn competence, with the specific characteristics of learning styles. These models aim to support personalized learning, the adaptation of teaching strategies, and the development of reflective and autonomous learning. Learning styles are analyzed through the lens of cognitive, motivational, and behavioral self-regulation mechanisms, which significantly contribute to the development of the learning to learn competence, essential for lifelong learning.